Sistem Administrasi Kerja Praktik Mahasiswa Fakultas Teknik Universitas Pahlawan Tuanku Tambusai Berbasi Websiste - Pangeran Otda Madani; Munti, Novi Yona Sidratul; Deddy Gusman (Jurnal Inovasi Teknik Informatika, 2023)
The need for a website is not only in government or office. Higher education as the birthplace of intelligent and responsive generations must also be better prepared to deal with technological advances. This also applies to Hero University located in Kampar Regency. The administrative process in the actual work of engineering school students is still done manually, the verification and signing process is often forced by teachers and leaders outside the school, which prolongs the process. administrative. The method used in this study is the cascade method. The system is also built using the Laravel framework and object-oriented programming with the addition of the bootstrap CSS framework. The result of this study is that the actual job administration website, Faculty of Engineering, Pahlawan Tuanku Tambusai University, helps engineering students to perform practical job administration more easily and in no time.